2005
DOI: 10.1086/498049
|View full text |Cite
|
Sign up to set email alerts
|

Polygyny, Fertility, and Savings

Abstract: Sub-Saharan Africa has a high incidence of polygyny. Countries in this region are also characterized by large age gaps between husbands and wives, high fertility, and the payment of a brideprice at marriage. In monogamous countries, on the other hand, the bride's parents traditionally give a dowry (negative brideprice) at marriage. Sub-Saharan Africa is also the poorest region of the world. In this paper I ask whether banning polygyny could play any role for development in Sub-Saharan Africa. Since this experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(177 citation statements)
references
References 25 publications
9
158
1
2
Order By: Relevance
“…women in worse condition become later wives to polygynous men [71,72]. This may help explain why we see the opposite effect at the group level; polygynous societies have higher total fertility rates than monogamous ones [28]. These differences seem to be driven primarily by the higher demand for women, which reduces the number of unmarried women and pushes their age at first birth down, thus extending women's reproductive lifespan [73].…”
Section: Re-evaluating the Empirical Literaturementioning
confidence: 90%
See 1 more Smart Citation
“…women in worse condition become later wives to polygynous men [71,72]. This may help explain why we see the opposite effect at the group level; polygynous societies have higher total fertility rates than monogamous ones [28]. These differences seem to be driven primarily by the higher demand for women, which reduces the number of unmarried women and pushes their age at first birth down, thus extending women's reproductive lifespan [73].…”
Section: Re-evaluating the Empirical Literaturementioning
confidence: 90%
“…Several studies have reported that women in polygynous households have lower fertility than their monogamous counterparts in the same society [26,27], but polygynous societies tend to have higher fertility than monogamous ones [28]. Some evolutionary scholars interpret this higher fertility as being against women's interests, but are ambiguous whether it is specifically against her fitness interests [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polygyny is not an issue of the past. We still observe polygynous marriage at a rate of up to 55 % in many sub-Saharan African countries (Tertilt 2005). For example, the percentage of married men in a polygynous union is 55 % in Cameroon and 40 % in Senegal and Burkina Faso.…”
Section: Introductionmentioning
confidence: 89%
“…In a similar vein, Tertilt (2005) uses an overlapping-generations model to examine if polygyny can explain the low levels of development in sub-Saharan Africa. In her model, the return on daughters is positive due to bride price, while the return on sons is zero.…”
Section: Polygamymentioning
confidence: 99%